PENGARUH FINANCIAL TECHNOLOGY TERHADAP PROFITABILITAS PERBANKAN YANG TERCATAT DI BURSA EFEK INDONESIA TAHUN 2021 – 2023 - Alma Libera; Vina Anggilia Puspita (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
This study aims to analyze the effect of financial technology (fintech) utilization on the profitability of banking companies listed on the Indonesia Stock Exchange during the period 2021-2023. This financial technology utilization is seen from the use of mobile banking technology, while banking company profitability is seen from the Return on Assets (ROA) generated by the banking company. This study uses a quantitative approach using simple linear regression analysis techniques. The sampling technique used purposive sampling with a total sample of 3 banking companies. Data collection techniques used by the researcher were documentation and literature study. The data used are secondary data, namely annual reports listed on the Indonesia Stock Exchange and sustainability reports containing data needed for 2021-2023. The results of this study indicate that the use of mobile banking technology has a positive and significant effect on bank profitability as measured by Return on Assets (ROA).